The Impact of Financial Disclosure on Investment Decisions in Capital Markets - Rusdiah Hasanuddin; Nadya Nurhidayah Nurdin; Nurasia Natsir (International Journal of Economics, Management and Accounting, 2025)
This study examines the relationship between corporate financial disclosure and investment decisions by shareholders and investors in capital markets. Using a comprehensive dataset of 486 publicly listed companies from multiple stock exchanges over a five-year period (2018-2022), we investigate how the quality, scope, and timing of financial disclosures influence investment behaviors, pricing efficiency, and capital allocation. Through multiple regression analysis, structural equation modeling, and panel data techniques, we find that higher disclosure quality is significantly associated with increased trading volumes (β=0.42, p<0.01), lower bid-ask spreads (β=-0.38, p<0.01), and reduced stock price volatility (β=-0.31, p<0.01). Our analysis reveals that voluntary disclosures beyond regulatory requirements have a stronger impact on institutional investor decisions compared to retail investors. Additionally, the study documents that forward-looking financial information and segment reporting have particularly strong effects on investment decisions during periods of market uncertainty. The findings contribute to disclosure theory and provide empirical evidence for regulators considering disclosure policy reforms, corporate executives formulating communication strategies, and investors developing investment frameworks that incorporate disclosure quality assessment. The study addresses the causality challenge through instrumental variable estimation and difference-in-differences analysis of regulatory changes, enhancing the robustness of the identified relationships.